1999
DOI: 10.1074/jbc.274.45.32342
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Element and a TEF-2-like Element Activate the Major Histocompatibility Complex Class II Transactivator in B-lymphocytes

Abstract: Major histocompatibility complex (MHC) class II molecules play a central role in immune responses, and transcription of this family of genes requires the MHC class II transactivator (CIITA). CIITA has four promoters, which are transcribed in a tissue-specific manner. CIITA promoter III is constitutively active in mature B-lymphocytes. This report now describes the minimal 319-base pair promoter region necessary for maximal transcriptional activity in B-lymphocytes. Ultraviolet light and dimethylsulfate in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 49 publications
6
64
0
1
Order By: Relevance
“…However, candidate intermediates can be predicted based on what is known of GM-CSF signaling and CIITA promoter regulation. The cis regions important for activation of PIII have been identified in B and T cells (15,35,36,39). In addition, a region upstream of PIII responsible for CIITA expression in response to IFN-␥ has been identified and involves binding of STAT-1, but not IRF-1 (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, candidate intermediates can be predicted based on what is known of GM-CSF signaling and CIITA promoter regulation. The cis regions important for activation of PIII have been identified in B and T cells (15,35,36,39). In addition, a region upstream of PIII responsible for CIITA expression in response to IFN-␥ has been identified and involves binding of STAT-1, but not IRF-1 (40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sites were found in promoter III that showed differential occupation in CIITA-expressing cells and in Jar cells. A recent report by Ghosh et al (50) showed that two sites in promoter III, which they designated ARE-1 and ARE-2, were critical for transcriptional activity. They also found several other sites of protein/DNA interaction in pIII, a region designated site A (Ϫ27 to Ϫ18).…”
Section: Discussionmentioning
confidence: 99%
“…However, these same regions remain unoccupied in Jar cells treated with IFN-␥, suggesting that the factors that bind these sites are either absent or unable to access the promoter in this trophoblast cell line. Recently, Ghosh et al (50) identified several regions of in vivo occupancy within pIII that were important for B cell expression. Three of these regions, Ϫ142 to Ϫ133, Ϫ66 to Ϫ56, and Ϫ27 to Ϫ18, correspond to the sites we have identified.…”
Section: Factor Assembly At Ciita Promoters III and Iv Does Not Occurmentioning
confidence: 99%
“…Characterization of the CIITA type III promoter by Ghosh et al (43) revealed that the sequences between Ϫ319 and ϩ1 (relative to the start site of transcription) are sufficient for optimal transcriptional activity in the human B lymphoma line Raji. To study CIITA type III promoter activity in L1210 cells, a DNA fragment spanning the region of the human type III promoter from Ϫ322 to ϩ1 was generated by PCR amplification of Raji genomic DNA and cloned into the firefly luciferase vector pGL3-basic (Promega) to generate pCIITA proIII (322)luc.…”
Section: Activity Of the Ciita Type III Promoter In Class Ii-negativementioning
confidence: 99%